Nucleoside Diphosphate Kinase-C Suppresses cAMP Formation in Human Heart Failure. Issue 9 (28th February 2017) - Abu-Taha, Issam H.; Heijman, Jordi; Hippe, Hans-Jörg; Wolf, Nadine M.; El-Armouche, Ali; Nikolaev, Viacheslav O.; Schäfer, Marina; Würtz, Christina M.; Neef, Stefan; Voigt, Niels; Baczkó, István; Varró, András; et al.
Abstract : Background: Chronic heart failure (HF) is associated with altered signal transduction via β-adrenoceptors and G proteins and with reduced cAMP formation. Nucleoside diphosphate kinases (NDPKs) are enriched at the plasma membrane of patients with end-stage HF, but the functional consequences of this are largely unknown, particularly for NDPK-C. Here, we investigated the potential role of NDPK-C in cardiac cAMP formation and contractility. Methods: Real-time polymerase chain reaction, (far) Western blot, immunoprecipitation, and immunocytochemistry were used to study the expression, interaction with G proteins, and localization of NDPKs. cAMP levels were determined with immunoassays or fluorescent resonance energy transfer, and contractility was determined in cardiomyocytes (cell shortening) and in vivo (fractional shortening). Results: NDPK-C was essential for the formation of an NDPK-B/G protein complex. Protein and mRNA levels of NDPK-C were upregulated in end-stage human HF, in rats after long-term isoprenaline stimulation through osmotic minipumps, and after incubation of rat neonatal cardiomyocytes with isoprenaline. Isoprenaline also promoted translocation of NDPK-C to the plasma membrane. Overexpression of NDPK-C in cardiomyocytes increased cAMP levels and sensitized cardiomyocytes to isoprenaline-induced augmentation of contractility, whereas NDPK-C knockdown decreased cAMP levels. In vivo, depletion of NDPK-C in zebrafish embryos caused cardiac edema and ventricular dysfunction. NDPK-B knockout mice had unaltered NDPK-C expression but showed contractile dysfunction and exacerbated cardiac remodeling during long-term isoprenaline stimulation. In human end-stage HF, the complex formation between NDPK-C and Gαi2 was increased whereas the NDPK-C/Gαs interaction was decreased, producing a switch that may contribute to an NDPK-C–dependent cAMP reduction in HF. Conclusions: Our findings identify NDPK-C as an essential requirement for both the interaction between NDPK isoforms and between NDPK isoforms and G proteins. NDPK-C is a novel critical regulator of β-adrenoceptor/cAMP signaling and cardiac contractility. By switching from Gαs to Gαi2 activation, NDPK-C may contribute to lower cAMP levels and the related contractile dysfunction in HF. Abstract : Supplemental Digital Content is available in the text.